تطبيق كتاب المفتاح للعلوم لتعليم النحو في المعهد "منبع الحكم للبنات" جاتيرجو جومبانج - Kholis, Nur; Ubaidillah, Burhanuddin; Fathur Rohman, Fathur (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2023)
This article examines the implementation of the Kitab Al Miftah Lil'ulum in Nahwu Learning at the Mamba'ul Hikam Putri Islamic Boarding School, Jatirejo Jombang. This study aims to determine how the learning of nahwu using the Kitab al miftah is the inhibiting and supporting factors for the Implementation of the Kitab Al Miftah Lil'ulum in Nahwu Learning at the Putri Mamba'ul Hikam Islamic Boarding School, Jombang. This research uses descriptive qualitative research with the type of case study research. Data collection techniques by observation, interviews and documentation. The results of his research were the implementation of the book al miftah lil 'ulum in learning nahwu at the women's boarding school mamba'ul hikam jatirejo jombang which consisted of four volumes, in general it can be said to be quite good this is proven by the results of observations which this book can understand nahwu to the students easily. The inhibiting factors for learning the almiftah book at the Mamba'ul Hikam female Islamic boarding school are the lack of learning time, the lack of teaching staff, teachers who do not master the material and the understanding of different students. The supporting factors for learning the Kitab al Miftah at the Mamba'ul Hikam female Islamic boarding school are the ease of licensing in the dissemination of the method and the enthusiasm of the students in memorizing because this method consists of nadhoms that can be sung.